Epoxy group-containing compound and application thereof
By introducing epoxy-containing compounds into the liquid crystal alignment agent, using their cross-linking and rigid groups during the curing process, the problems of deterioration of the liquid crystal alignment film and charge accumulation of liquid crystal display elements under long-term driving are solved, and the liquid crystal alignment film is realized. Higher photoelectric properties, mechanical strength and stability.
Patent Information
- Application Number
- CN202411620300.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-14
AI Technical Summary
When the conventional liquid crystal display element is continuously driven for a long time, the liquid crystal orientation film deteriorates due to heat or light, the display quality decreases, and it is easy to produce afterimage due to charge accumulation.
The compound containing epoxy groups is used as the component of the liquid crystal alignment agent. The compound opens the ring during the curing process and generates crosslinking to enhance the chemical stability and mechanical strength of the film. At the same time, rigid groups such as naphthalene ring are introduced to improve the liquid crystal Orientation uniformity.
The photoelectric performance, mechanical strength and stability of the liquid crystal orientation film are improved, the service life of the liquid crystal display element is extended, the charge accumulation and afterimage are reduced, and the display quality is improved.
Smart Images

Figure BDA0005133272590000021 
Figure BDA0005133272590000031 
Figure BDA0005133272590000032
Abstract
Description
Technical Field
[0001] The present application relates to an epoxy-containing compound, a liquid crystal alignment agent, and also to their preparation methods and applications, belonging to the technical field of liquid crystal alignment materials. Background Art
[0002] In recent years, research on improving display quality and reducing power consumption, led by the high-precision of liquid crystal display elements, has been continuously carried out, and the scope of use of liquid crystal display elements has also been expanding. As a result, a liquid crystal display element with higher display quality and no decrease in display quality even when driven continuously for a long time is required. However, the previously known liquid crystal display element with a liquid crystal alignment film formed by polyamic acid or polyimide has been pointed out to have degradation problems such as degradation of the liquid crystal alignment film due to heat or light when driven continuously for a long time, resulting in degradation of display quality; in addition, if charges accumulate in the liquid crystal alignment film, even a short-term drive is prone to produce residual images, and these accumulated charges will affect the display in the form of disordered liquid crystal orientation and residual images, significantly reducing the display quality of the liquid crystal element. Therefore, there is a strong demand for a liquid crystal alignment film with less accumulation of direct current charge (DC), fast release, and high long-term reliability.
[0003] Patent WO2019 / 078502 discloses a specific liquid crystal alignment film with good orientation, high film strength, and excellent durability; as a method to shorten the disappearance time of residual images, patent WO2018 / 030489 proposes an alignment film prepared by using a polymer containing a specific structure, so that the liquid crystal display element can obtain a higher voltage retention rate and a fast relaxation of accumulated charge. However, with the high performance of liquid crystal display elements, the performance required by the liquid crystal alignment film has also become strict, and what is needed is a liquid crystal alignment film with balanced performance. Summary of the invention
[0004] In order to solve the problem mentioned in the background technology, the present application provides an epoxy-containing compound, which can be used in a liquid crystal alignment agent to improve the photoelectric performance, mechanical strength and stability of a liquid crystal alignment film.
[0005] In a first aspect, the present application provides an epoxy-containing compound having a structural formula represented by formula (1):
[0006]
[0007] In the above formula (1), the group represented by R is selected from H, alkyl, halogenated alkyl, cyclohexyl, phenyl, and biphenyl.
[0008] On the other hand, the present application provides a liquid crystal alignment agent, which includes a polymer A and a compound B containing an epoxy group.
[0009] Furthermore, the polymer A is at least one of polyamic acid and polyimide.
[0010] Furthermore, the epoxy-containing compound B is at least one of the epoxy-containing compounds described in the above general formula (1).
[0011] Furthermore, the liquid crystal alignment agent further includes a solvent C. Wherein, the solvent C is an organic solvent.
[0012] On the other hand, the present application provides a liquid crystal alignment film, which is prepared from the above-mentioned liquid crystal alignment agent.
[0013] On the other hand, the present application provides a liquid crystal display element, which includes the above-mentioned liquid crystal alignment film.
[0014] The present invention has the following beneficial effects:
[0015] 1. The epoxy group contained in the present invention can be ring-opened and cross-linked during the curing process of the alignment film, thereby enhancing the chemical stability and mechanical strength of the cured film; and the introduction of a rigid group such as a naphthalene ring into the epoxy compound can improve the uniformity of the liquid crystal orientation. Therefore, by utilizing the synergistic effect of the two, the epoxy compound of the present invention is used in a liquid crystal alignment agent to improve the photoelectric performance, mechanical strength and stability of the liquid crystal alignment film.
[0016] 2. The present invention introduces a special epoxy-containing compound into the liquid crystal alignment agent, thereby improving the photoelectric properties, mechanical strength and stability of the liquid crystal alignment film, and improving the voltage holding rate (VHR) of the liquid crystal display element containing the liquid crystal alignment film, improving friction resistance, improving long-term reliability, and excellent liquid crystal orientation. In addition, the direct current charge (DC) is released quickly, the direct current charge (DC) accumulation is reduced, and the overall performance is improved. DETAILED DESCRIPTION
[0017] The present invention is explained and described in more detail below so that those skilled in the art can have a deeper understanding of the advantages of the technical solution of the present invention. It should be understood that the following description is only exemplary and does not limit its content.
[0018] The present application provides an epoxy-containing compound having a structural formula represented by formula (1):
[0019]
[0020] In the above formula (1), the group represented by R is selected from H, alkyl, halogenated alkyl, cyclohexyl, phenyl, and biphenyl.
[0021] Furthermore, the alkyl group is preferably a C1-C5 alkyl group, wherein the C1-C5 alkyl group may be a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, or the like.
[0022] Furthermore, the haloalkyl group is preferably a C1-C5 haloalkyl group, and the C1-C5 haloalkyl group may be a trifluoromethyl group, a trifluoroethyl group, or the like.
[0023] Furthermore, the compound of the present invention contains structures such as epoxy groups and naphthyl groups. When the epoxy group-containing compound is added to the liquid crystal alignment agent and then solidified to form a liquid crystal alignment film, the epoxy group undergoes a ring-opening reaction and generates crosslinking, which can improve the surface compactness of the liquid crystal alignment film and thus improve the friction resistance of the liquid crystal alignment film. At the same time, the epoxy group-containing compound itself has rigid groups such as naphthalene rings, which can further improve the orientation uniformity of the liquid crystal alignment film, thereby improving the overall performance of the entire liquid crystal alignment film, and making it more reliable and stable.
[0024] Furthermore, in the epoxy-containing compound, the stronger the rigidity of the R group, the more uniform the orientation and the higher the hardness of the obtained liquid crystal alignment film. If the stability of the R group is stronger, the transmittance of the obtained liquid crystal alignment film is higher and the electrical performance is better. Based on the perspective of balanced performance of the liquid crystal alignment film, the R group is preferably a C1-C5 alkyl, a C1-C5 haloalkyl, a cyclohexyl or a biphenyl group, and more preferably CH2CH3, CF3, a cyclohexyl or a biphenyl group.
[0025] Furthermore, the epoxy-containing compound of the present invention is preferably selected from any one of the compounds represented by the following formulas (B-1) to (B-4):
[0026]
[0027]
[0028] On the other hand, the present application provides a method for preparing the above-mentioned epoxy-containing compound, wherein the reaction formula when R is hydrogen is:
[0029]
[0030] Wherein, when R is alkyl, halogenated alkyl, cyclohexyl, phenyl or biphenyl, the reaction formula is:
[0031]
[0032] On the other hand, the present application provides a liquid crystal alignment agent, wherein the liquid crystal alignment agent includes a polymer A. The polymer A is at least one of polyamic acid and polyimide.
[0033] Furthermore, the polyamic acid and polyimide can be selected from polyimides or polyamic acids disclosed in the prior art and can be used for liquid crystal alignment agents, or can be prepared by themselves. The polyamic acid can be obtained by reacting a tetracarboxylic dianhydride compound CA with a diamine compound DA, and the polyimide can be obtained by dehydration and ring closure of the polyamic acid.
[0034] Furthermore, the tetracarboxylic dianhydride compound CA includes at least one of aliphatic tetracarboxylic dianhydride and aromatic tetracarboxylic dianhydride. These tetracarboxylic dianhydride compounds can be used alone or in combination of two or more.
[0035] Preferably, the aliphatic tetracarboxylic dianhydride is selected from at least one of cyclobutanetetracarboxylic dianhydride, 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,3-dimethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-cyclopentanetetracarboxylic dianhydride, 1,2,3,4-cyclohexanetetracarboxylic dianhydride, 2,3,5-tricarboxycyclopentylacetic dianhydride, 3,4-dicarboxy-1-cyclohexylsuccinic dianhydride, 3,4-dicarboxy-1,2,3,4-tetrahydro-1-naphthalenesuccinic dianhydride, bicyclo[3.3.0]octane-2,4,6,8-tetracarboxylic dianhydride, 1,2,3,4-butanetetracarboxylic dianhydride, 2,3,4,5-tetrahydrofurantetracarboxylic dianhydride, and bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride.
[0036] Preferably, the aromatic tetracarboxylic dianhydride is selected from at least one of pyromellitic dianhydride, 3,3,4,4'-biphenyltetracarboxylic dianhydride, 2,2,3,3'-biphenyltetracarboxylic dianhydride, 2,3,3,4'-biphenyltetracarboxylic dianhydride, 3,3,4,4'-dibenzophenonetetracarboxylic dianhydride, 2,3,3,4'-dibenzophenonetetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)ether dianhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 4,4'-(4,4'-isopropyldiphenyloxy)phthalic anhydride, 4,4'-(hexafluoroisopropylene)phthalic anhydride, and 4,4'-isopropyl-bis(phthalic anhydride).
[0037] Furthermore, the diamine compound DA may include, for example, aliphatic diamines, alicyclic diamines, aromatic diamines and other diamines. Similarly, these diamine compounds may be used alone or in combination of two or more.
[0038] Preferably, the aliphatic diamine may be at least one of m-xylylenediamine, 1,3-propylenediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine and the like.
[0039] Preferably, the alicyclic diamine may be at least one of 1,4-diaminocyclohexane, 4,4'-methylenebis(cyclohexylamine), 1,3-bis(aminomethyl)cyclohexane, and the like.
[0040] Preferably, the aromatic diamines include, for example, p-phenylenediamine, 2,5-dimethyl-p-phenylenediamine, m-phenylenediamine, 2,4-dimethyl-m-phenylenediamine, 2,5-diaminotoluene, 2,6-diaminotoluene, 4-aminobenzylamine, 2-(4-aminophenyl)ethylamine, 4-(2-(methylamino)ethyl)aniline, 4-(2-aminoethyl)aniline, 2-(6-aminonaphthyl)ethylamine, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dimethoxy-4,4'-diaminobiphenyl, biphenyl, 3,3'-dihydroxy-4,4'-diaminobiphenyl, 2,2'-difluoro-4,4'-diaminobiphenyl, 3,3'-difluoro-4,4'-diaminobiphenyl, 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 3,3'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 3,4'-diaminobiphenyl, 4,4'-diaminobiphenyl, 3,3'-diaminobiphenyl, 2,2'-diaminobiphenyl, 2,3'-diaminobiphenyl, 1,5-diaminonaphthalene, 1,6-diaminonaphthalene, 1,7-diaminonaphthalene, 2 ,5-diaminonaphthalene, 2,6-diaminonaphthalene, 2,7-diaminonaphthalene, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 4,4'-thiodiphenylamine, 3,3'-thiodiphenylamine, 1,4-bis(4-aminophenyl)benzene, 1,3-bis(4-aminophenyl)benzene, 2,2'-bis(4-aminophenyl)hexafluoropropane, 2,2'-bis(3-aminophenyl)hexafluoropropane, 2,2'-bis(3-amino-4-methylphenyl)hexafluoropropane, 2,2'-bis(4-aminophenyl)hexafluoropropane at least one of 2,6-diaminopyridine, 3,4-diaminopyridine, 2,4-diaminopyrimidine, 3,6-diaminocarbazole, N-methyl-3,6-diaminocarbazole, 1,4-bis-(4-aminophenyl)-piperazine, 3,6-diaminoacridine, N-ethyl-3,6-diaminocarbazole and N-phenyl-3,6-diaminocarbazole.
[0041] Preferably, the other diamines include compounds having the following formula DA-1 and the following formula DA-2:
[0042]
[0043] Production method of polyamic acid:
[0044] The preparation of the polyamic acid of the present invention can adopt the method disclosed in the prior art. For example, the preparation method of the polyamic acid can include the following steps: dissolving the tetracarboxylic dianhydride compound CA and the diamine compound DA in a solvent, and performing a polymerization reaction at -20°C to 150°C, more preferably at 0 to 100°C, preferably for 0.1 to 24 hours, more preferably for 0.5 to 12 hours.
[0045] Further, the solvent for the polymerization reaction of the tetracarboxylic dianhydride compound CA and the diamine compound DA may be the same as or different from the solvent in the liquid crystal alignment agent, and the solvent in the polymerization reaction is not particularly limited, as long as it can dissolve the reactants and the product. Preferably, the solvent includes but is not limited to N, N-dimethylformamide, N, N-dimethylacetamide, N-methylpyrrolidone, N-methylcaprolactam, N-methyl-2-pyrrolidone, γ-butyrolactone, methyl ethyl ketone, cyclohexanone, cyclopentanone, 4-hydroxy-4-methyl-2-pentanone, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, ethylene glycol methyl ethyl ether, ethylene glycol dimethyl ether, dimethyl sulfoxide, etc. At least one. These solvents can be used alone or in combination. In addition, since water inhibits the polymerization reaction and causes the generated polyamic acid to hydrolyze, it is preferred to use a solvent that has been dehydrated and dried. From the perspective of preventing the polymer from precipitating and easily obtaining a high molecular weight, based on 100 parts by weight of the total amount of the tetracarboxylic dianhydride compound CA and the diamine compound DA, the amount of the solvent used in the polymerization reaction is 200-2000 parts by weight, for example, 200 parts by weight, 500 parts by weight, 1000 parts by weight, 1500 parts by weight, 1800 parts by weight, and 2000 parts by weight; more preferably, the amount of the solvent used in the polymerization reaction is 500 parts by weight to 1800 parts by weight.
[0046] As described above, after the polymerization reaction is completed, a reaction solution in which polyamic acid is dissolved is obtained. The reaction solution can be directly used for the preparation of a liquid crystal alignment agent, or the polyamic acid contained in the reaction solution can be separated and then used for the preparation of a liquid crystal alignment agent, or the separated polyamic acid can be purified and then used for the preparation of a liquid crystal alignment agent.
[0047] The separation and purification of polyamic acid can be carried out by fully stirring the obtained polyamic acid solution while injecting a poor solvent to precipitate the polymer and recover the polymer by filtering. The polymer recovered by filtering is dissolved in a solvent again and precipitated again and filtered and recovered. This process is repeated many times to reduce impurities in the polymer, and then dried at room temperature or heated to obtain a purified polyamic acid solid. The poor solvent is not particularly limited and can be alcohols, ketones, esters, ethers, halogenated hydrocarbons, hydrocarbons, etc. Specific examples of such poor solvents include methanol, ethanol, isopropanol, cyclohexanol, ethylene glycol, propylene glycol, 1,4-butanediol, triethylene glycol, ethylene glycol monomethyl ether, ethyl lactate, butyl lactate, acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, methyl acetate, ethyl acetate, butyl ester, methyl methoxypropionate, ethyl ethoxypropionate, diethyl oxalate, diethyl malonate, ethyl ether, ethylene glycol methyl ether, ethylene glycol ethyl ether, ethyl At least one of glycol n-propyl ether, ethylene glycol isopropyl ether, ethylene glycol n-butyl ether, ethylene glycol dimethyl ether, ethylene glycol ethyl ether acetate, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, tetrahydrofuran, dichloromethane, 1,2-dichloroethane, 1,4-dichlorobutane, trichloroethane, chlorobenzene, o-dichlorobenzene, hexane, heptane, octane, benzene, toluene, xylene, etc.
[0048] Polyimide manufacturing method:
[0049] Polyimide can be manufactured by imidization of polyamic acid. It can be synthesized by dehydration ring closure (imidization) of polyamic acid as described above. The dehydration ring closure of polyamic acid can be carried out by heating the polyamic acid, or by dissolving the polyamic acid in an organic solvent, adding a dehydrating agent and an alkaline catalyst to the solution, and heating as required. Chemical imidization can carry out imidization reaction at a relatively low temperature, and is not easy to cause the molecular weight of the polymer to decrease during the imidization process, so it is preferred.
[0050] Chemical imidization can be carried out as follows: in polyamic acid solution, add dehydrating agent and alkaline catalyst, as dehydrating agent, can use acid anhydrides such as acetic anhydride, propionic anhydride, trifluoroacetic anhydride.Wherein, when using acetic anhydride, reaction is easier to purify when finishing, so preferred.In addition, alkaline catalyst, can use tertiary amines such as pyridine, colidine, lutidine, triethylamine, but is not limited to these.As the organic solvent used in the dehydration ring-closure reaction, can be enumerated as the solvent used in the synthesis of polyamic acid.
[0051] The imidization reaction is carried out at a temperature of -20°C to 140°C, for example -20°C, -10°C, 0°C, 20°C, 40°C, 60°C, 80°C, 100°C, 120°C, 140°C, more preferably 0°C to 100°C. The reaction time can be carried out within 1 to 100 hours, for example 1 hour, 5 hours, 10 hours, 30 hours, 50 hours, 80 hours, 100 hours. The amount of the imidization alkaline catalyst is 0.5 to 30 mole times of the polyamic acid group, for example, 0.5 mole times, 1 mole times, 5 mole times, 10 mole times, 15 mole times, 20 mole times, 25 mole times, 30 mole times, preferably 2 to 20 mole times, and the amount of the dehydrating agent is 1 to 50 mole times of the polyamic acid group, for example, 1 mole times, 5 mole times, 10 mole times, 15 mole times, 20 mole times, 25 mole times, 30 mole times, 35 mole times, 40 mole times, 45 mole times, 50 mole times, preferably 3 to 30 mole times. The imidization rate of the obtained polymer does not necessarily have to reach 100%, and can be controlled by adjusting the amount of catalyst, temperature, reaction time, etc.
[0052] Since the added catalyst and the like remain in the polyimide solution obtained after the imidization reaction, it is preferred that the obtained polyimide polymer is recovered by the following means, redissolved in an organic solvent, and used for preparation of a liquid crystal aligning agent.
[0053] The polyimide solution obtained above can be put into a poor solvent to precipitate the polymer, and the polymer can be recovered by filtration. The polymer recovered by precipitation is dissolved in the solvent again and reprecipitated and recovered. This process is repeated many times to reduce impurities in the polymer. The polymer is then dried at room temperature or heated to obtain a purified polymer solid.
[0054] The poor solvent is consistent with the poor solvent mentioned in the method for producing polyamic acid.
[0055] The molecular weight of the polyimide or polyamic acid used in the liquid crystal alignment agent of the present invention is preferably 2000 to 500000, for example, 2000, 5000, 10000, 50000, 100000, 150000, 200000, 250000, 300000, 350000, 400000, 450000, 500000, more preferably 5000 to 300000, and even more preferably 10000 to 100000.
[0056] Solution viscosity of polyamic acid and polyimide:
[0057] The polyamic acid and polyimide polymers used in the present invention, when respectively formulated into solutions with a concentration of 6wt%, preferably have a solution viscosity of 10 to 500mPa·s, for example, 10mPa·s, 20mPa·s, 50mPa·s, 100mPa·s, 300mPa·s, 500mPa·s, and more preferably have a solution viscosity of 20 to 300mPa·s.
[0058] The solution viscosity (mPa·s) of the above polymer is tested by using a benign solvent for the polymer (e.g., N-methyl-2-pyrrolidone, γ-butyrolactone, etc.) to prepare a 6 wt% polymer solution, and then measuring the viscosity of the solution at 25°C using an E-type rotational viscometer.
[0059] Furthermore, the liquid crystal alignment agent further comprises an epoxy-containing compound B, and the epoxy-containing compound B is at least one of the epoxy-containing compounds described in the above general formula (1).
[0060] Further, the liquid crystal alignment agent further includes a solvent C. Wherein, the solvent C is an organic solvent, and the solvent C is preferably at least one of N-methylpyrrolidone, N-methyl-2-pyrrolidone, γ-butyrolactone, γ-butyrolactam, 4-hydroxy-4-methyl-2-pentanone, ethylene glycol monomethyl ether, butyl lactate, butyl acetate, methyl methoxypropionate, ethyl ethoxypropionate, ethylene glycol methyl ether, ethylene glycol ethyl ether, ethylene glycol n-propyl ether, ethylene glycol isopropyl ether, ethylene glycol n-butyl ether, ethylene glycol dimethyl ether, ethylene glycol ethyl ether acetate, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, N,N-dimethylformamide, N,N-dimethylacetamide, butyl cellosolve, and the like.
[0061] Furthermore, based on 100 parts by weight of the polymer A, the epoxy-containing compound B is used in an amount of 0.5 to 20 parts by weight, such as 0.5, 1, 1.5, 2, 5, 10, 15, 20, preferably 1 to 20, more preferably 1 to 10. When the content of the epoxy-containing compound is too low, there will be disadvantages such as low hardness, poor friction resistance, low voltage holding rate, and poor reliability.
[0062] Further, based on 100 parts by weight of the polymer A, the amount of the solvent C is 500 to 5000 parts by weight, for example, 500 parts, 1000 parts, 1500 parts, 2000 parts, 2500 parts, 3000 parts, 3500 parts, 4000 parts, 4500 parts, 5000 parts, preferably 1000 to 3000 parts, more preferably 1000 to 2000 parts. Within this amount range, the liquid crystal alignment agent has good printability.
[0063] Furthermore, the preparation of the liquid crystal alignment agent of the present invention is simple, and all that is required is to mix the components evenly.
[0064] On the other hand, the present application provides a liquid crystal alignment film, which is prepared from the above-mentioned liquid crystal alignment agent.
[0065] Preparation method of liquid crystal alignment film:
[0066] The liquid crystal alignment film of the present invention can be obtained by coating the liquid crystal alignment agent of the present invention on a substrate, followed by calcination, alignment and other treatments.
[0067] As the substrate for coating the liquid crystal aligning agent of the present invention, there is no other special limitation as long as it is a substrate with high transparency, and glass substrates, acrylic substrates, silicon nitride substrates, polycarbonate substrates, polyurethane substrates, trimethylpentene substrates, cellulose triacetate substrates, cellulose acetate butyrate substrates, etc. can be used. In addition, from the perspective of simplifying the process, it is preferred to use a substrate with an ITO electrode for driving liquid crystals, etc. In addition, in a reflective liquid crystal display element, if it is only a single-sided substrate, an opaque material such as a silicon wafer can be used, and the electrode at this time can also use a material that reflects light such as aluminum.
[0068] The coating method of the liquid crystal alignment agent of the present invention includes printing methods such as screen printing, offset printing, flexographic printing, spraying, spin coating, inkjet, etc. From the perspective of production efficiency, printing is often used in industrial production and can also be appropriately used in the present invention.
[0069] After the liquid crystal alignment agent is applied by the above-mentioned coating method, the formed coating film is baked to become a cured film. The drying process after the liquid crystal alignment agent is applied is not necessary, and the time from coating to baking for each substrate is not fixed. The drying is sufficient as long as the solvent is removed until the shape of the coating film is not deformed due to the transportation of the substrate, etc., and there is no particular limitation on the drying means. For example, it can be listed that the drying is carried out at 50 to 120°C, preferably 60 to 100°C for 1 minute to 10 minutes, preferably 2 to 5 minutes, and then baked and cured at 150 to 300°C, preferably 200 to 240°C for 5 to 120 minutes, preferably 10 to 30 minutes. The thickness of the film after curing is not particularly limited. When the film thickness is too thin, the reliability of the liquid crystal display element may be reduced, so it is 5 to 300nm, preferably 10 to 200nm.
[0070] Examples of a method for performing an alignment treatment on a film include a brushing method and a photo-alignment treatment method. However, the liquid crystal alignment agent of the present invention is more effective when used in a rubbing alignment treatment method.
[0071] On the other hand, the present application provides a liquid crystal display element, which includes the above-mentioned liquid crystal alignment film.
[0072] Method for making liquid crystal display element:
[0073] The liquid crystal display element of the present invention is obtained by obtaining a substrate having a liquid crystal alignment film obtained from the above-mentioned liquid crystal alignment agent, and then preparing a liquid crystal cell by a known method, and using the liquid crystal cell to prepare an element.
[0074] The specific method for making a liquid crystal display element is as follows: first, prepare a pair of substrates with a liquid crystal alignment film, then spread a spacer on the liquid crystal alignment film of a single substrate, adhere it to another substrate with the liquid crystal alignment film surface as the inner side, and inject liquid crystal under reduced pressure and seal it. Alternatively, liquid crystal can be dripped onto the surface of the liquid crystal alignment film with the spacer, and then the substrates can be adhered and sealed. The thickness of the spacer at this time is preferably 1 to 30 um, and more preferably 2 to 10 um.
[0075] The present invention is further described below in conjunction with specific examples, but the present invention is not limited to the following examples. The methods are conventional methods unless otherwise specified. The materials can be purchased from public commercial channels unless otherwise specified.
[0076] The molecular weights of the polyimide and polyamic acid obtained in the following examples were measured by GPC method (Shimadzu Corporation, Japan, gel permeation chromatography), with N-methylpyrrolidone as the mobile phase, and the obtained molecular weights were all weight average molecular weights (Mw).
[0077] The components used in the following synthesis examples and embodiments are referred to as follows:
[0078] NMP: N-methyl-2-pyrrolidone;
[0079] BC: Butyl Cellosolve;
[0080] Diamine compound DA:
[0081]
[0082] Tetracarboxylic dianhydride compound CA:
[0083]
[0084]
[0085] Epoxy-containing compounds:
[0086]
[0087]
[0088] Synthesis example 1
[0089] Into a 500mL four-necked flask with a stirring device, N2 was introduced, and DA-1 3.0g (0.013mol), DA-3 11.21g (0.053mol), and NMP 172.21g were added in sequence. After they were dissolved, CA-2 9.71g (0.033mol) and CA-3 6.47g (0.033mol) were added, and the reaction was carried out at room temperature for 24 hours. After the reaction was completed, NMP and BC were added to prepare a polyamic acid solution PAA-1, in which the polymer content in the solution was 6wt%, the NMP content was 70wt%, and the BC content was 24wt%. The GPC test polymer molecular weight Mw was 68045g / mol.
[0090] Synthesis example 2
[0091] Into a 500mL four-necked flask with a stirring device, N2 was introduced, and DA-1 3.0g (0.013mol), DA-4 10.57g (0.053mol), and NMP 173.85g were added in sequence. After they were dissolved, CA-1 7.40g (0.033mol) and CA-2 9.71g (0.033mol) were added, and the reaction was carried out at room temperature for 24 hours. After the reaction was completed, NMP and BC were added to prepare a polyamic acid solution PAA-2, in which the polymer content in the solution was 6wt%, the NMP content was 70wt%, and the BC content was 24wt%. The GPC test polymer molecular weight Mw was 66315g / mol.
[0092] Synthesis example 3
[0093] Into a 500mL four-necked flask with a stirring device, N2 was introduced, and DA-1 3.0g (0.013mol), DA-4 10.57g (0.053mol), and NMP 168.61g were added in sequence. After they were dissolved, CA-2 9.71g (0.033mol) and CA-3 6.47g (0.033mol) were added, and the reaction was carried out at room temperature for 24 hours. After the reaction was completed, NMP and BC were added to prepare a polyamic acid solution PAA-3, in which the polymer content in the solution was 6wt%, the NMP content was 70wt%, and the BC content was 24wt%. The GPC test polymer molecular weight Mw was 67663g / mol.
[0094] Synthesis example 4
[0095] Into a 500mL four-necked flask with a stirring device, N2 was introduced, and DA-2 5.0g (0.012mol), DA-3 10.05g (0.047mol), and NMP 167.49g were added in sequence. After they were dissolved, CA-2 8.70g (0.030mol) and CA-3 5.80g (0.030mol) were added, and the reaction was carried out at room temperature for 24 hours. After the reaction was completed, NMP and BC were added to prepare a polyamic acid solution PAA-4, in which the polymer content in the solution was 6wt%, the NMP content was 70wt%, and the BC content was 24wt%. The GPC test polymer molecular weight Mw was 67378g / mol.
[0096] Synthesis example 5
[0097] Into a 500mL four-necked flask with a stirring device, N2 was introduced, and DA-2 5.0g (0.012mol), DA-4 9.48g (0.047mol), and NMP 168.96g were added in sequence. After they were dissolved, CA-1 6.63g (0.030mol) and CA-2 8.70g (0.030mol) were added, and the reaction was carried out at room temperature for 24 hours. After the reaction was completed, NMP and BC were added to prepare a polyamic acid solution PAA-5, in which the polymer content in the solution was 6wt%, the NMP content was 70wt%, and the BC content was 24wt%. The GPC test polymer molecular weight Mw was 68815g / mol.
[0098] Synthesis example 6
[0099] Into a 500mL four-necked flask with a stirring device, N2 was introduced, and DA-2 5.0g (0.012mol), DA-4 9.48g (0.047mol), and NMP 164.28g were added in sequence. After they were dissolved, CA-2 8.70g (0.030mol) and CA-3 5.80g (0.030mol) were added, and the reaction was carried out at room temperature for 24 hours. After the reaction was completed, NMP and BC were added to prepare a polyamic acid solution PAA-6, in which the polymer content in the solution was 6wt%, the NMP content was 70wt%, and the BC content was 24wt%. The GPC test polymer molecular weight Mw was 67967g / mol.
[0100] Synthesis Example 7
[0101] Into a 500mL four-necked flask with a stirring device, N2 was introduced, and DA-1 3.0g (0.013mol), DA-3 11.21g (0.053mol), and NMP 177.46g were added in sequence. After they were dissolved, CA-1 7.40g (0.033mol) and CA-2 9.71g (0.033mol) were added. After reacting at room temperature for 24 hours, pyridine 15.66g (0.198mol) and acetic anhydride 33.67g (0.33mol) were added in sequence, and the reaction was carried out at 50°C for 5 hours for imidization reaction. Then, the reaction solution was put into ethanol for precipitation, and filtered to obtain a white powdery solid. After the obtained white solid was washed with ethanol, the white solid was dissolved in NMP, and then precipitated in ethanol, filtered, and the polyimide was refined. Finally, the refined polyimide was vacuum dried for standby use. The vacuum-dried polyimide solid was first dissolved in NMP, and then BC was added to prepare a polyimide solution PI-1. The polymer content in the solution was 6wt%, the NMP content was 70wt%, and the BC content was 24wt%. The GPC test showed that the polymer molecular weight Mw was 66876g / mol.
[0102] Synthesis example 8
[0103] Into a 500mL four-necked flask with a stirring device, N2 was introduced, and DA-2 5.0g (0.012mol), DA-3 10.05g (0.047mol), and NMP 172.19g were added in sequence. After they were dissolved, CA-1 6.63g (0.030mol) and CA-2 8.70g (0.030mol) were added. After reacting at room temperature for 24 hours, pyridine 14.00g (0.177mol) and acetic anhydride 30.12g (0.295mol) were added in sequence, and the reaction was carried out at 50°C for 5 hours to carry out imidization reaction. Then, the reaction solution was put into ethanol for precipitation, and filtered to obtain a white powdery solid. After the obtained white solid was washed with ethanol, the white solid was dissolved in NMP, and then precipitated in ethanol, filtered, and the polyimide was refined. Finally, the refined polyimide was vacuum dried for standby use. The vacuum-dried polyimide solid was first dissolved in NMP, and then BC was added to prepare a polyimide solution PI-2. The polymer content in the solution was 6wt%, the NMP content was 70wt%, and the BC content was 24wt%. The GPC test showed that the polymer molecular weight Mw was 67096g / mol.
[0104] Synthesis example 9
[0105] Into a 500mL four-necked flask with a stirring device, N2 was introduced, and DA-3 7.0g (0.033mol), DA-4 6.60g (0.033mol), and NMP 164.28g were added in sequence. After they were dissolved, CA-2 9.70g (0.033mol) and CA-3 6.46g (0.033mol) were added, and the reaction was carried out at room temperature for 24 hours. After the reaction was completed, NMP and BC were added to prepare a polyamic acid solution PAA-7, in which the polymer content in the solution was 6wt%, the NMP content was 70wt%, and the BC content was 24wt%. The GPC test polymer molecular weight Mw was 66125g / mol.
[0106] Synthesis of Synthesis Example 10B-1
[0107]
[0108] 20 g (0.059 mol) of 2,6-naphthalenediamine-bis-4-phenylamine and an appropriate amount of methanol were added to a three-necked flask, and the temperature was raised to 50°C. A mixture of 21.83 g (0.236 mol) of epichlorohydrin and methanol was added to a constant pressure dropping funnel and slowly added dropwise. After the addition of epichlorohydrin was completed, the reaction was kept warm for 6 hours. During this period, TLC was used to monitor the completion of the reaction. An appropriate amount of triethylamine solution was slowly added dropwise with a constant pressure dropping funnel for the ring-closing reaction of epichlorohydrin. After the reaction was completed for 2 hours, a mixed solution of 7.61 g (0.118 mol) of 1-chloroethane and methanol was added dropwise through a constant pressure dropping funnel, and the temperature was raised to 80°C. After the reaction was reacted for 3 hours, the reaction solvent was removed by distillation under reduced pressure, and then the concentrate was dissolved in dichloromethane. The organic phase was washed with deionized water until neutral, and the solvent was removed by distillation under reduced pressure again to obtain the target product B-1, a light yellow transparent liquid with a yield of 85%.
[0109] B-1 NMR information is as follows:
[0110] 1 HNMR (500MHz, CDCl3): δ: 7.74(s,2H), 7.46(s,2H), 7.10(s,2H), 7.07-7.04(m,4H), 6.71-6.68(m,4H), 3. 69-3.62(m,8H), 3.36-3.34(d,4H), 3.30-3.27(d,4H), 2.93-2.92(d,4H), 2.84-2.83(d,4H), 1.29(s,6H).
[0111] Synthesis of Synthesis Example 11B-2
[0112]
[0113] 20 g (0.059 mol) of 2,6-naphthalenediamine-bis-4-phenylamine and an appropriate amount of methanol were added to a three-necked flask, and the temperature was raised to 50°C. A mixture of 21.83 g (0.236 mol) of epichlorohydrin and methanol was added to a constant pressure dropping funnel and slowly added dropwise. After the addition of epichlorohydrin was completed, the reaction was allowed to proceed for 6 hours. During this period, the reaction was monitored by TLC. After the completion of the reaction, an appropriate amount of triethylamine solution was slowly added dropwise with a constant pressure dropping funnel for the ring-closing reaction of epichlorohydrin. After the reaction was completed for 2 hours, a methanol solution of 12.33 g (0.118 mol) of chlorotrifluoromethane was added dropwise through a constant pressure dropping funnel, and the temperature was raised to 80°C. After the reaction was continued for 3 hours, the reaction solvent was removed by distillation under reduced pressure, and then the concentrated solution was dissolved in dichloromethane. The organic phase was washed with deionized water until neutral, and the solvent was removed by distillation under reduced pressure again to obtain the target product B-2 as a light yellow transparent liquid with a yield of 80%.
[0114] B-2 NMR information is as follows:
[0115] 1 HNMR (500MHz, CDCl3): δ: 7.96(s,2H), 7.81(s,2H), 7.49(s,2H), 7.32-7.29(m,4H), 6.69-6.67(m,4H), 3.68(s,4H), 3.36-3.34(d,4H),
[0116] 3.30-3.27(d,4H), 2.93-2.92(d,4H), 2.84-2.83(d,4H).
[0117] Synthesis of Synthesis Example 12B-3
[0118]
[0119]
[0120] 20 g (0.059 mol) of 2,6-naphthalenediamine-bis-4-phenylamine and an appropriate amount of methanol were added to a three-necked flask, and the temperature was raised to 50°C. A mixture of 21.83 g (0.236 mol) of epichlorohydrin and methanol was added to a constant pressure dropping funnel and slowly added dropwise. After the addition of epichlorohydrin was completed, the reaction was allowed to proceed for 6 hours. During this period, TLC was used to monitor the completion of the reaction. An appropriate amount of triethylamine solution was slowly added dropwise with a constant pressure dropping funnel for the ring-closing reaction of epichlorohydrin. After the reaction was completed for 2 hours, a mixed solution of 13.99 g (0.118 mol) of chlorocyclohexane and methanol was added dropwise through a constant pressure dropping funnel, and the temperature was raised to 80°C. After the reaction was continued for 3 hours, the reaction solvent was removed by distillation under reduced pressure, and then the concentrated solution was dissolved in dichloromethane. The organic phase was washed with deionized water until neutral, and the solvent was removed by distillation under reduced pressure again to obtain the target product B-3 as a light yellow transparent liquid with a yield of 81%.
[0121] B-3 NMR information is as follows:
[0122] 1 HNMR (500MHz, CDCl3): δ: 7.76 (s, 2H), 7.39 (s, 2H),
[0123] 7.02-7.00(m,4H), 6.94(s,2H), 6.70-6.68(m,4H), 3.77(s,2H), 3.68(s,4H), 3.36-3.34(d,4H), 3.30-3.27(d,4H), 2.93-2.92(d,4H) , 2.84-2.83(d,4H), 1.96-1.94(d,4H), 1.70-1.68(d,4H), 1.62-1.60(d,2H), 1.57-1.55(d,4H), 1.42-1.40(d,4H), 1.35-1.32(d,2H).
[0124] Synthesis Example 13B-4
[0125]
[0126] 20 g (0.059 mol) of 2,6-naphthalenediamine-bis-4-phenylamine and an appropriate amount of methanol were added to a three-necked flask, and the temperature was raised to 50°C. A mixture of 21.83 g (0.236 mol) of epichlorohydrin and methanol was added to a constant pressure dropping funnel and slowly added dropwise. After the addition of epichlorohydrin was completed, the reaction was allowed to proceed for 6 hours. During this period, the reaction was monitored by TLC. After completion, an appropriate amount of triethylamine solution was slowly added dropwise with a constant pressure dropping funnel for the ring-closing reaction of epichlorohydrin. After the reaction was completed for 2 hours, a mixed solution of 22.26 g (0.118 mol) of 4-chlorobiphenyl and methanol was added dropwise through a constant pressure dropping funnel, and the temperature was raised to 80°C. After the reaction was continued for 3 hours, the reaction solvent was removed by distillation under reduced pressure, and then the concentrated solution was dissolved in dichloromethane. The organic phase was washed with deionized water until neutral, and the solvent was removed by distillation under reduced pressure again to obtain the target product B-4 as a light yellow transparent liquid with a yield of 86%.
[0127] B-4 NMR information is as follows:
[0128] 1 HNMR (500MHz, CDCl3): δ: 7.86 (s, 2H), 7.72 (s, 2H),
[0129] 7.67-7.64(m,4H), 7.61-7.58(m,4H), 7.45-7.35(m,6H), 7.20(s,2H),
[0130] 7.17-7.14(m,4H), 7.10-7.08(m,4H), 6.76-6.74(m,4H), 3.68(s,4H),
[0131] 3.36-3.34(d,4H), 3.30-3.27(d,4H), 2.93-2.92(d,4H), 2.84-2.83(d,4H).
[0132] Example 1
[0133] A liquid crystal aligning agent 1 was obtained by stirring 100.00 g of the polyimide solution PAA-1 obtained in Synthesis Example 1 and 0.03 g of the epoxy group-containing compound B-1 at room temperature (25° C.) for 3 hours.
[0134] Example 2-18
[0135] 100.00 g of different types of polyimide solutions or polyamic acid solutions and epoxy-containing compounds obtained in the synthesis example were stirred at room temperature (25° C.) for 3 hours to obtain a series of liquid crystal alignment agents. The specific selection of polyimide solutions or polyamic acid solutions and epoxy-containing compounds is shown in Table 1 below.
[0136] Comparative Examples 1-4
[0137] 100.00 g of the polyamic acid solution obtained in the synthesis example and the epoxy-containing compound (if any) were stirred at room temperature (25° C.) for 3 hours to obtain a series of liquid crystal alignment agents. The specific selection of the polyamic acid solution and the epoxy-containing compound is shown in Table 1 below.
[0138] Table 1
[0139]
[0140]
[0141] Application Example 1
[0142] Each liquid crystal alignment agent in each embodiment and comparative example is filtered through a PTFE membrane filter, and then coated on a glass substrate having a conductive film composed of an ITO electrode by spin coating to form a pre-coating layer. Thereafter, pre-curing is performed on a heating plate at a temperature of 80°C for a time of 5 minutes, and main curing is performed in a circulation oven at a temperature of 230°C for a time of 60 minutes. After friction alignment treatment, a liquid crystal alignment film can be obtained.
[0143] Application Example 2
[0144] Take the two glass substrates with liquid crystal alignment films prepared above, with the film surface on the inner side, the friction direction is opposite, and a 4um spacer is sandwiched in the middle. The two glass substrates are combined and the surrounding parts are bonded with a sealant to prepare an empty box. Liquid crystal MLC-7028 (Merck) is injected into the empty box by the reduced pressure injection method, the injection hole is sealed, and polarizers are attached to the outer sides of the substrate to prepare an FFS driven liquid crystal unit.
[0145] Performance Verification
[0146] The FFS driven liquid crystal unit manufactured as above was evaluated for various test items in the following manner.
[0147] (1) Evaluation of friction resistance
[0148] The upper and lower substrates of the FFS-driven liquid crystal unit made of the liquid crystal alignment agent of the embodiment and the comparative example were attached with polarizers with orthogonal polarization axis directions, and then the FFS-driven liquid crystal unit was placed on the backlight plate, and the friction stripes of the FFS-driven liquid crystal unit lit at a voltage near the threshold (the voltage near the relative transmittance of the FFS-driven liquid crystal unit is 10%) were observed with a 5x magnifying glass. The lighter the friction stripes, the better the friction resistance of the alignment film.
[0149] The evaluation results of friction resistance are as follows:
[0150] √: No friction streaks when observed under a magnifying glass, good friction resistance;
[0151] ○: Slight friction streaks are observed under a magnifying glass, but no friction streaks are observed with the naked eye, indicating average friction resistance.
[0152] △: There are slight friction streaks when observed with the naked eye, and the friction resistance is poor;
[0153] ×: There are obvious friction streaks when observed with the naked eye, and the friction resistance is extremely poor.
[0154] (2) Evaluation of Liquid Crystal Orientation
[0155] The FFS-driven liquid crystal cells made of the liquid crystal alignment agents of the examples and comparative examples were observed under a microscope at a magnification of 50 times to see if there were abnormal areas that changed light and dark when the voltage of 5 V was turned on and off. The alignment was rated "excellent" when no abnormal area was observed, and "poor" when abnormal areas were observed.
[0156] (3) Evaluation of residual DC charge (RDC)
[0157] The FFS-driven liquid crystal unit prepared with the liquid crystal alignment agent of the embodiment and the comparative example was placed in an oven at 60°C, and a 5V DC voltage was applied to the FFS-driven liquid crystal unit for 1 hour. After short-circuiting for 1 second, the voltage of the FFS-driven liquid crystal unit was tested, and the voltage value after 10 minutes was taken as the RDC of the FFS-driven liquid crystal unit.
[0158] (4) Evaluation of voltage holding ratio (VHR)
[0159] After applying 5V voltage to the FFS-driven liquid crystal cells made of the liquid crystal alignment agents of the examples and comparative examples with an application time of 60 microseconds and a span of 167 milliseconds, the voltage holding ratio was measured 167 milliseconds after the application was released. During the measurement, the temperature of the FFS-driven liquid crystal cell was set to 25°C and 60°C, respectively.
[0160] The evaluation results are shown in Table 2.
[0161] Table 2
[0162]
[0163]
[0164] It can be seen from Examples 1 to 5 in Table 2 above that as the amount of the epoxy-containing compound added increases, the friction resistance of the liquid crystal alignment film gradually increases, the orientation of the liquid crystal display element and the release performance of the DC charge become better, and at the same time, the voltage holding rate of the liquid crystal display element increases, and the thermal stability of the voltage holding rate is better. When the amount of the epoxy-containing compound added reaches a certain proportion, the friction resistance and the orientation of the liquid crystal display element remain good, but the voltage holding rate of the liquid crystal display element begins to decrease and the thermal stability deteriorates.
[0165] By comparing the examples and comparative examples in Table 2 above, it can be seen that the friction resistance of the liquid crystal alignment film to which the epoxy-containing compound of the present invention is added is improved, the orientation of the liquid crystal display element to which the epoxy-containing compound of the present invention is added is improved, the release rate of DC charge is improved, the voltage holding rate is improved, and the electrical properties and thermal stability are better.
[0166] Therefore, the liquid crystal alignment agent containing the epoxy-containing compound of the present invention can significantly improve the friction resistance and liquid crystal orientation of the liquid crystal alignment film, and can also improve the voltage holding rate and thermal stability of the liquid crystal display element. Therefore, the liquid crystal display element obtained by the liquid crystal alignment agent of the present invention has better reliability and photoelectric performance, and can be applied to long-term continuous driving, high heat conditions and scenes with high display quality.
Claims
1. A compound containing an epoxy group, characterized in that It has the structural formula represented by formula (1): In the formula (1), R represents H, an alkyl group, a halogenated alkyl group, a cyclohexyl group, a phenyl group or a biphenyl group.
2. The compound according to claim 1, characterized in that In formula (1), the alkyl group is a C1-C5 alkyl group, and the haloalkyl group is a C1-C5 haloalkyl group.
3. The compound according to claim 1, characterized in that Any one selected from the compounds having structures (B-1) to (B-4) below:
4. A liquid crystal alignment agent, characterized in that: The invention comprises a polymer and an epoxy-containing compound, wherein the epoxy-containing compound is at least one of the epoxy-containing compounds according to any one of claims 1 to 3.
5. The liquid crystal alignment agent according to claim 4, characterized in that: The polymer is at least one of polyamic acid and polyimide.
6. The liquid crystal alignment agent according to claim 4, characterized in that: Also included is a solvent, which is an organic solvent.
7. The liquid crystal alignment agent according to claim 6, characterized in that: The solvent is at least one of N-methylpyrrolidone, N-methyl-2-pyrrolidone, γ-butyrolactone, γ-butyrolactam, 4-hydroxy-4-methyl-2-pentanone, ethylene glycol monomethyl ether, butyl lactate, butyl acetate, methyl methoxypropionate, ethyl ethoxypropionate, ethylene glycol methyl ether, ethylene glycol ethyl ether, ethylene glycol n-propyl ether, ethylene glycol isopropyl ether, ethylene glycol n-butyl ether, ethylene glycol dimethyl ether, ethylene glycol ethyl ether acetate, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, N,N-dimethylformamide, N,N-dimethylacetamide, and butyl cellosolve.
8. The liquid crystal alignment agent according to any one of claims 4 to 7, characterized in that: Based on 100 parts by weight of the polymer, the epoxy group-containing compound is used in an amount of 0.5 to 20 parts by weight, and the solvent is used in an amount of 500 to 5000 parts by weight.
9. A liquid crystal alignment film, characterized in that: Made from the liquid crystal alignment agent described in any one of claims 4 to 8.
10. A liquid crystal display element, characterized in that: The invention comprises the liquid crystal alignment film according to claim 9.
Citation Information
Patent Citations
Liquid crystal aligning agent, liquid crystal alignment film and liquid crystal display element
WO2018030489A1
Liquid crystal alignment film and liquid crystal display device using same
WO2019078502A1
Liquid crystal orientation agent, liquid crystal orientation membrane and liquid crystal display element
CN108485683A
Arylamine compound, liquid crystal aligning agent prepared from arylamine compound, liquid crystal alignment film and liquid crystal display element
CN112225675A
Eepoxy group-containing compound, liquid crystal aligning agent and preparation method and application thereof
CN114014845A